PP.LB02.23: HYPERTENSION IS THE MAIN FACTOR IN PATIENTS WITH SPONTANEOUS CORONARY ARTERY DISSECTION LONG-TERM STUDY. (June 2015) - Capin, E.; Gomez, A.; Cortina, R.; Llosa, J.; Gallego, P.; Bernardo, J.C.; Gorostidi, M.
Abstract : Objective: Spontaneous coronary artery dissection (SCAD) is an acute coronary event of uncertain origin. The clinical features and prognosis are not sufficiently characterized. Figure. No caption available. Design and method: We retrospectively analyzed the cases of coronary artery dissection (1998–2014). In 6 cases the characteristic angiographic findings (Table 1) are displayed, 30 cases were excluded due to iatrogenic. Results: The mean age was 54.6 years, all women, the presentation in all STEMI and heart failure cases, the affected vessel in most cases was the left anterior descending (LAD), however, found multivessel disease in 16.6% (angiographic characteristics are shown in Table 1). IVUS was performed in two patients to confirm the diagnosis. The presumed etiology of spontaneous dissection was intense exercise in 37.6%, with a frequency of 18.8% rupture of atherosclerotic plaque, hormonal influences related to pregnancy and contraception and Sjögren's syndrome were found. In one case, no obvious risk factor was identified. In 66% of cases the initial conservative treatment and surgical revascularization 18.8% were associated with good hospital outcome, while percutaneous coronary intervention previous implant 3 level TCI DA proximal stent and postpartum immediately, and after eight years at CD by intracoronary hematoma, presented new event in the first 24 hours, so that medical treatment is decided. During a mean follow-up period of 60 months, 1 patient was exitus, 66% of patients remained completely asymptomatic, whereas the patient with a history of dissection in the immediate postpartum treated with stent recurrence at 8 years. Fibromuscular dysplasia of the iliac artery in 2 of 4 (50%) of femoral angiograms, before placement of the closure device in the carotid artery and the patient will carotid dissection identified himself. Conclusions: SCAD affects a young population, mostly women, often appears as STEMI and /or heart failure. Although hospital mortality is low regardless of initial treatment, percutaneous coronary intervention may be associated with complications. The fibromuscular dysplasia could be a potentially related agent. The increased availability of coronary angiography and imaging techniques such as IVUS and OCT contribute to the increase in the diagnosis of this entity